Our sisters the plants? notes from phylogenetics and botany on plant kinship blindness. (2nd December 2021) - Bouteau, François; Grésillon, Etienne; Chartier, Denis; Arbelet-Bonnin, Delphine; Kawano, Tomonori; Baluška, František; Mancuso, Stefano; Calvo, Paco; Laurenti, Patrick
ABSTRACT: Before the upheaval brought about by phylogenetic classification, classical taxonomy separated living beings into two distinct kingdoms, animals and plants. Rooted in 'naturalist' cosmology, Western science has built its theoretical apparatus on this dichotomy mostly based on ancient Aristotelian ideas. Nowadays, despite the adoption of the Darwinian paradigm that unifies living organisms as a kinship, the concept of the "scale of beings" continues to structure our analysis and understanding of living species. Our aim is to combine developments in phylogeny, recent advances in biology, and renewed interest in plant agency to craft an interdisciplinary stance on the living realm. The lines at the origin of plant or animal have a common evolutionary history dating back to about 3.9 Ga, separating only 1.6 Ga ago. From a phylogenetic perspective of living species history, plants and animals belong to sister groups. With recent data related to the field of Plant Neurobiology, our aim is to discuss some socio-cultural obstacles, mainly in Western naturalist epistemology, that have prevented the integration of living organisms as relatives, while suggesting a few avenues inspired by practices principally from other ontologies that could help overcome these obstacles and build bridges between different ways of connecting to life.